(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The 12th conference Nano & Macro Mechanics was held in Prague, in September 16, 2021. The main objective of the conference is to bring together researchers, students and engineers devoting their work to comuting and experimental mechanics in different areas of engineering applications on a common platform. The conference key topics were following: • Testing of buildings materials at the nano, micro, mezzo and macro levels. • Destructive and non-destructive methods for determining the mechanical properties of buildings materials. • Relationships between material parameters. • Computational and experimental dynamics and mechanics. • Material research for steel, buildings materials, glass, woods, textiles and composites. • Analyses of constructions. • Computational methods for analyses of constructions and materials. Scientific comittee: Tomáš Plachý Pavel Tesárek Pavel Padevět Petr Bittnar Aleš Jíra Jan Vorel Bořek Patzák Michal Šejnoha Local organizing comittee: Petr Bittnar Tomáš Plachý Pavel Padevět Pavel Tesárek Tereza Plaček - Otcovská Ondřej Zobal Guarantor of the peer review process: Pavel Padevět Guarantor of the language editing: Tomáš Plachý